End-tidal carbon dioxide (ETCO2) and ventricular fibrillation amplitude spectral area (AMSA) for shock outcome prediction in out-of-hospital cardiac arrest. Are they two sides of the same coin?. (March 2021) - Frigerio, Laura; Baldi, Enrico; Aramendi, Elisabete; Chicote, Beatriz; Irusta, Unai; Contri, Enrico; Palo, Alessandra; Compagnoni, Sara; Fracchia, Rosa; Iotti, Giorgio; Oltrona Visconti, Luigi; Savastano, Simone; et al.
Abstract: Aim: Ventricular fibrillation amplitude spectral area (AMSA) and end-tidal carbon dioxide (ETCO2 ) are predictors of shock success, understood as restoration of an organized rhythm, and return of spontaneous circulation (ROSC). However, little is known about their combined use. We aimed to assess the prediction accuracy when combined, and to clarify if they are correlated in out of hospital cardiac arrest' victims. Materials and Methods: Records acquired by external defibrillators in out-of-hospital cardiac arrest patients of the Lombardia Cardiac Arrest registry were processed. The 1-min pre-shock ETCO2 median value (METCO2 ) was computed from the capnogram and AMSA (2–48 mV.Hz range) computed applying the Fast Fourier Transform to a 2-second pre-shock filtered ECG interval (0.5−30 Hz). Support Vector Machine (SVM) predictive models based on METCO2, AMSA and their combination were fit; results were given as the area under the curve (AUC) of the receiver operating characteristic (ROC) curves. Results: We considered 112 patients with 391 shocks delivered. METCO2 and AMSA were predictors of shock success [AUC (IQR) of the ROC curve: 0.59 (0.56−0.62); 0.68 (0.65−0.72), respectively] and of ROSC [0.56 (0.53−0.59); 0.74 (0.71−0.78), ]. Their combination in a SVM model increased the accuracy for predicting shock success [AUC (IQR) of the ROC curve: 0.71 (0.68−0.75)] and ROSC [0.77 (0.73−0.8)]. AMSA and METCO2 were significantly correlated only in patients who achieved ROSC (rho = 0.33 p = 0.03). Conclusions: AMSA and ETCO2 predict shock success and ROSC after every shock, and their predictive power increases if combined. Notably, they were correlated only in patients who achieved ROSC.